The Convention of Independent German-speaking Baptist Churches as a Regional and Border Area: A defined and constantly changing cultural space - Valdir Modes, Josemar (Vox Scripturae - Revista Teológica Internacional, 2025)
The study about the Convention of the German-speaking Independent Baptist Churches, and the churches that belong to it, shows the importance of analyzing the religious communities present in Brazil, which by their characteristics make up regional spaces, and manifest an intense cultural transit that is experienced and spread by them. Religious communities become small cultural regions and maintain these characteristic traditions